2022
DOI: 10.24018/ejbio.2022.3.1.309
|View full text |Cite
|
Sign up to set email alerts
|

Status and Association of BRCA1 and BRCA2 Mutation with Clinicopathological Features in Sudanese Patients with Breast Cancer

Abstract: Breast cancer is a real problem in Sudan. Onset at early age, presentation with late stage, and limited resources are characterizing national context of breast cancer in Sudan. Histopathology and cytology of breast cancer serve as tool to expand knowledge in order to improve prevention, management and quality of breast cancer patient life. The aim of this study was to find out prevalence of BRCA1 and BRCA2 among Sudanese patients and to investigate the association of BRCA1and BRCA2 genes with clinicopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…The age 30-45years was the most frequent age group 48.6% (17/35), followed by 46-60 years 40% (14/35). This agrees with Hamad et al [9], Babiker et al [10], Saleh et al [11], Juneja et al [12], who found the majority of breast cancer cases are in this age group.…”
Section: Discussionsupporting
confidence: 91%
“…The age 30-45years was the most frequent age group 48.6% (17/35), followed by 46-60 years 40% (14/35). This agrees with Hamad et al [9], Babiker et al [10], Saleh et al [11], Juneja et al [12], who found the majority of breast cancer cases are in this age group.…”
Section: Discussionsupporting
confidence: 91%